The Drosophila patched gene encodes a putative membrane protein required for segmental patterning. - Hooper, J.E.; Scott, M.P. (Cell, 1989)
The patched (ptc) gene is one of several segment polarity genes required for correct patterning within every segment of Drosophila. The absence of ptc gene function causes a transformation of the fate of cells in the middle part of each segment so that they form pattern elements characteristic of cells positioned around the segment border. Analysis of the mutant phenotype demonstrates that both segment and parasegment borders are included in the duplicated pattern of ptc mutants. We have cloned the ptc gene and deduced that the product is a 1286 amino acid protein with at least seven putative transmembrane alpha helices. ptc RNA is expressed in embryos in broad stripes of segmental periodicity that later split into two stripes per segment primordium. The pattern of expression does not directly predict the transformation seen in ptc mutant embryos, suggesting that ptc participates in cell interactions that establish pattern within the segment.